HOW INFLATION AFFECTS BALANCE SHEETS. - Sweeney, Henry W. (The Accounting Review, 1934)
Abstract Economists and accountants have looked at the prospect of inflation from different basic points of view. Some have thought principally of the effects that inflation will have upon business profits, hence upon employment and power to pay debts. Others have thought principally of effects upon real wages and the standard of living. And others have concentrated their attentions on effects upon accumulated capital, such as savings, or upon stock-market prices or public finance. But none seem to have given any thought at all to the effect that inflation is sure to have upon the ability of the economic key men to choose wise courses of economic action for people. In practical business life these key men are managers of business enterprises, whether large or small. These men may be filling roles of entrepreneurs, or they may be merely paid servants of real entrepreneurs. But in any case the direction of economic activity and the amount and intensity of it, are determined by these men. If they decide to produce more or less of certain products and services, then land, labor and capital will be employed for those purposes.